R-SUBGRUP NORMAL FUZZY NEAR-RING - Saman Abdurrahman (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
In this paper will be discussed R-subgroup normal fuzzy near-ring, with approach and    + 1  , for each .